Effects of precooling on thermoregulation during subsequent exercise - Bolster, D. R.; Trappe, S. W.; Short, K. R.; Scheffield-Moore, M.; Parcell, A. C.; Schulze, K. M.; Costill, D. L. (Medicine & Science in Sports & Exercise, 1999)
The purpose of this study was to examine the effect of a decreased body core temperature before a simulated portion of a triathlon (swim,15 min; bike, 45 min) and examine whether precooling could attenuate thermal strain and increase subjective exercise tolerance in a warm environment (26.6°C/60% relative humidity (rh)). Result: Precooling attenuated the rise in Tre (rectal temperature), but this effect was transient. Therefore, precooling is not recommended before a triathlon under similar environmental conditions.